Sensitivity to Shocks and Implicit Employment Protection in Family Firms - Carl Magnus Bjuggren (Research Institute of Industrial Economics (IFN), 2014)
In this study I present empirical evidence that employment in family firms is less sensitive to performance and product market fluctuations, both at the industry and at the firm level. This supports the idea that family firms are able to offer their employees implicit employment protection. Family firms are believed to have longer time horizons, and are as owners more easily identified with their company and its actions. These are features that could make family firms more cautious in terms of adjusting their employment. I confirm previous findings that family firms are less sensitive to sales fluctuations at the industry level and I show that this also holds for fluctuations in value added. I extend the analysis to show that family firms are less sensitive to unanticipated industry shocks by filtering out the trend component. When investigating idiosyncratic shocks to the firm, I find that family firms are less anxious to translate temporary shocks in performance into changes in employment. By using full population data from tax registers, I am able to identify all family firms, both listed and non-listed. This has previously not been feasible.
Keywords: D22; G32; J21; J23; L25; 330; Family Firms; Risk Sharing; Employment Protection; Shocks